Influencing mechanisms of microwave radiation duration on the efficiency of methane adsorption in coals - Yiliang HU; Yuan BAO; Jiahao MENG; Xueru CHEN; Tuo SHAN (Meitian dizhi yu kantan)
ObjectiveMicrowave radiation duration represents a critical factor in enhancing coalbed methane (CBM) recovery using microwave-aided methods. However, the influencing mechanism of microwave radiation duration on the efficiency of methane adsorption in coal seams remains unclear. This necessitates delving into the specific effects of microwave radiation duration on the adsorption efficiency and unveiling their intrinsic constraints. MethodsThis study investigated the No.2 coal seam in the Huangling mining area. The coal samples were irradiated for 0‒18 min using 700 W microwaves. Using experiments and analyses including isothermal adsorption, low-temperature liquid N2 adsorption, and Fourier transform infrared spectroscopy (FTIR), this study analyzed the changes in the methane adsorption capacity, microscopic pore structure, and molecular structure of coals under varying microwave radiation durations. Furthermore, it examined the correlation between the structural parameters and methane adsorption parameters of coals post-radiation using multivariate statistical analysis. Results and ConclusionsThe experimental results demonstrate that the methane adsorption capacity of coals initially decreased and then increased as the microwave radiation duration increased. The minimum methane adsorption capacity (only 14.94 cm3/g) was observed in the case of a microwave radiation duration of 12 min. Microwave radiation significantly affected the molecular structure of coals. With an increase in the microwave radiation duration, the response intensities of aliphatic structures (CH2/CH3), oxygen-containing functional groups, aromatic structures, and hydroxyl absorption bands in the coal samples decreased generally. In contrast, the aromaticity (Har/Hal) of the coal samples showed an increasing trend, and their overall molecular stability also increased. These findings indicate that microwave radiation altered the methane adsorption capacity of coals by reducing the degree of branching and promoting aromatic condensation. As the microwave radiation duration increased, the micropores in coals underwent pore expansion initially and then pore formation. Specifically, the specific surface area (SSA) of mesopores decreased first and then increased, while their pore volume (PV) showed an opposite trend. The Pearson correlation matrix and principal component analysis (PCA) revealed that the SSA of mesopores with sizes ranging from 2 nm to 10 nm is a key parameter that influences the efficiency of methane adsorption in coal seams. The results of this study can provide theoretical parameters such as optimal radiation duration for efficient CBM production using microwave-assisted methods while also laying a foundation for in-depth research on multi-parameter coupling mechanisms in the future. This study will promote the application of microwave radiation technology in CBM production growth projects.